2014
DOI: 10.1254/jphs.13r06cr
|View full text |Cite
|
Sign up to set email alerts
|

Chrono-biology, Chrono-pharmacology, and Chrono-nutrition

Abstract: Molecular mechanisms of the circadian clock systemThe circadian clock system has been widely maintained in many species, from prokaryotes to mammals. "Circadian" means "around [a] day" in Latin, and therefore "circadian rhythm" refers to a cycle of approximate 24 h. The earth rotates once every 24 h, and the circadian system has evolved to adjust functions and behavior to this cycle in order to efficiently utilize sunlight for photosynthesis in the case of plants and cyanobacteria and to obtain food in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 182 publications
(137 reference statements)
0
66
0
Order By: Relevance
“…The SCN clock is mainly entrained by light-dark stimuli, and it regulates the peripheral clocks. The peripheral clocks are entrained by pharmacological agents, food nutrients, and mental or physical stress [15][16][17][18][19]. The SCFAs produced by the microbiota also entrain the circadian clock [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCN clock is mainly entrained by light-dark stimuli, and it regulates the peripheral clocks. The peripheral clocks are entrained by pharmacological agents, food nutrients, and mental or physical stress [15][16][17][18][19]. The SCFAs produced by the microbiota also entrain the circadian clock [20].…”
Section: Introductionmentioning
confidence: 99%
“…Chrono-nutrition is the science of nutrition, which is based on chronobiology. Hormonal secretion and the metabolism and absorption of nutrients have circadian variations [16]. Therefore, some food components have the most effective intake timing [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Rodent peripheral clock oscillation is entrained by a restricted feeding schedule2122 and also by scheduled exercise232425. Recent reports have demonstrated that insulin release is a critical step in the entrainment of the mouse peripheral clock by restricted feeding2627.…”
mentioning
confidence: 99%
“…It is also proposed that previous models addressed the body adaptation process as an open-loop systems instead as a closed-loop one [11].Therefore, although theoretical models provide a good insight in weight control process, there are other external and internal factors, which affect macronutrient metabolization and energy flux balances and that should be considered. For instance, new insights from the domain of chrono-nutrition indicate that, the rate of energy absorption varies in time [35,36]. These recent insights determine the best time to consume meals and the suitable meal proportions and its impact on bodyweight Appl.…”
mentioning
confidence: 99%